2019
DOI: 10.1177/0037549719873969
|View full text |Cite
|
Sign up to set email alerts
|

A mimicking technique of back pressure in the hardware-in-the-loop simulation of a fuel control unit

Abstract: In the hardware-in-the-loop (HIL) simulation of the fuel control unit (FCU) for aero-engines, the back pressure has a great impact on the metered fuel, thus influencing the confidence of simulation.During the practical working process of an aero-engine, the back pressure of FCU is influenced by the combined effect of the pressure of combustion chamber, the resistance of spray nozzles, and the resistance of the distribution valve. There is a need to study the mimicking technique of FCU back pressure. This paper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…The numerical results confirmed that the larger the input current to the torque motor, the faster the fuel metering valve responded. In [13], the effect of the FMU back pressure, namely the pressure downstream of the FMU, on the metered fuel was investigated using an AMESim model. It was found that the rate of metered fuel decreased with the back pressure increase.…”
Section: Figure 1 Aircraft Control Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…The numerical results confirmed that the larger the input current to the torque motor, the faster the fuel metering valve responded. In [13], the effect of the FMU back pressure, namely the pressure downstream of the FMU, on the metered fuel was investigated using an AMESim model. It was found that the rate of metered fuel decreased with the back pressure increase.…”
Section: Figure 1 Aircraft Control Systemmentioning
confidence: 99%
“…The pilot in the cockpit can change the thrust level by acting on a throttle lever as shown in Fig. 1 [9,13]. In particular, by acting on the throttle lever, the pilot stage of the fuel metering valve (which is typically a two-stage servovalve), controlled by the Electronic Control Unit (ECU), changes the pressures acting on the main-stage spool ends, thus changing the spool displacement, which in turn changes the flow rate delivered into the combustion chamber.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, the effects of back pressure and other nonlinear factors on pressure difference across metering valve have been researched. Yuan et al [52] researched the effect of the back pressure on the differential pressure. Chen et al [53] proposed the differential pressure fluctuation was the result of the dead zone in the zone-relay link.…”
Section: Influence Factorsmentioning
confidence: 99%
“…The hardware-in-the-loop (HIL) test provides an effective platform by testing actual components of a system along with virtual computer-based simulation models in real time [31,32]. By this means, the test quality is enhanced, the design cycle is shortened and the reliability of the tested components is improved.…”
Section: Hardware-in-the-loop Testmentioning
confidence: 99%